Pulse-profile Modeling and Spin–Orbit Alignment in a Suzaku Sample of Accreting X-Ray Binary Pulsars - Silas G. T. Laycock; Rigel C. Cappallo; Pragati Pradhan; Dimitris M. Christodoulou; Biswajit Paul (The Astrophysical Journal)
We report pulse-profile modeling of a sample of 23 X-ray binary pulsars observed with the Suzaku X-ray satellite. These pulsars have spin periods ranging from 0.7 to 9400 s, and their X-ray emission is powered by the accretion from their stellar companions. We fitted each individual pulse profile with the Polestar geometric model, which accounts for X-ray emission from two hot spots modeled as a simple combination of fan+pencil beam components, including an approximation for gravitational light bending. In 14 of 21 cases, our measurements of the inclinations of the pulsar spin axes broadly agree with the corresponding inclinations of the orbital planes of the binary systems determined by various other means, a striking outcome with a mere 6 × 10 ^−7 probability of occurring by chance. The implications of our study are as follows: (a) apparently, accretion torques have had time to erase spin–orbit misalignment caused by supernova kicks in two-thirds of the systems; (b) many X-ray binary pulsars have dominant dipolar surface magnetic fields, in contrast to the recently reported exotic configurations in millisecond pulsars; and (c) if the binary inclinations can be determined by pulse-profile modeling, even for a subset of the ∼200 known X-ray binary pulsars, most of which orbital inclinations are as yet poorly constrained, it raises the prospect of tightening dramatically ongoing neutron-star mass determinations. This is because masses in binary systems overwhelmingly come from an orbital-mechanics formulation (Kepler’s third law), in which the dominant source of uncertainty is the inclination of the orbital plane.